Pengaruh Strategi Card Sort terhadap Keterampilan Membaca Bahasa Arab Siswa - Muizzudin, Mochammad; Fuady, Siti Tsamrotul; Suhaili, Ahmad (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Arabic language learning, particularly in reading skills (qirā’ah), continues to face challenges in Islamic schools, including low student engagement and limited variety in instructional strategies. This study aims to analyze the effect of the Card Sort strategy on improving the reading skills of eighth-grade students at MTsN 2 Lebak. Employing a quantitative approach with a quasi-experimental design (nonequivalent control group design), the study involved 43 students divided into experimental and control groups. Data were collected through observation, interviews, tests, and documentation. The data were analyzed using an independent sample t-test with SPSS software. The findings revealed a significant difference between the post-test mean scores of the experimental group (68.81) and the control group (54.52), with a t-value of 3.547 and a significance level of p = 0.001 (p < 0.05). These results indicate that the Card Sort strategy effectively enhances students’ reading skills. The implication suggests that active and collaborative learning strategies such as Card Sort offer a relevant alternative in Arabic language instruction to foster student engagement and improve learning outcomes.